Tanacetum species: Bridging empirical knowledge, phytochemistry, nutritional value, health benefits and clinical evidence - Khatib, Sohaib; Sobeh, Mansour; Faraloni, Cecilia; Bouissane, Latifa (Frontiers in Pharmacology, 2023)
The Tanacetum genus consists of 160 accepted flowering species thriving throughout temperate regions, mainly in the Mediterranean Basin, northern America, and southwestern and eastern Asia. Tanacetum species bear a long-standing record of use in the folk medicine of indigenous tribes and communities worldwide, along with manifold applications in traditional cuisines, cosmeceuticals, and agricultural fields. Over the past three decades, 241 bioactive compounds have been isolated from almost twenty species, including phenolic acids, flavonoids, coumarins, fatty acids and alkanes, aldehydes, volatile compounds, and naphthoquinones. Some unique compounds have also been identified, such as the ceramides Tanacetamide (A-D) from T. artemisioides, pyrethrins from T. cinerariifolium, and sesquiterpene lactones from several species. However, these phytoconstituents are still poorly studied despite in vitro clues highlighting their colossal pharmacological properties, especially as hypotensive, neuroprotective, anticancer, and antimicrobial agents. Scientific studies have validated some traditional claims of the plant, such as antidiabetic, anticancer, anthelmintic, insecticide, antioxidant, and hepatoprotective activities, as well as against festering wounds, skin ulcers, urinary tract infections, and sexually transmitted diseases. Other ethnomedicinal uses for arthritis, gout, rheumatism, anemia, and as a litholytic, antivenom and diaphoretic have not yet been supported and would constitute the subject of further research. This review aimed to collate and critically summarize the current state of knowledge regarding the ethnobotanical uses, phytochemistry, biological activities, toxicity, and clinical trials of the genus Tanacetum to provide insights and directions for future studies and promote the valorization of the plant in the pharmaceutical, food, and agricultural fields.